Analysis of Changes in Malondialdehyde (MDA) and Lactate Dehydrogenase (LDH) Levels After a 30 km Cycling Event in The Makassar Cycling Community - Andi Eka Nur Wahyu; Irfan Idris; Djohan Aras; Andi Wardihan Sinrang; Ilhamjaya Patellongi; Nukhrawi Nawir (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study looks at the changes in MDA and LDH levels after a 30 km cycling event in the Makassar cycling community. This research is a pre-experimental with a one-group pretest-posttest design on 30 male cyclists aged 30-60 years. The pre-test was carried out the day before the cycling event, and then the post-test was carried out 2 hours after the 30 km cycling event. Blood samples were tested using the ELISA Kit. Data were analyzed using the Wilcoxon test to see the effect of a 30 km cycling event on changes in MDA and LDH levels. Spearman correlation test to see the correlation between changes in MDA levels and LDH. The results of the study found that the 30 km cycling event had a significant effect on changes in MDA levels due to lipid peroxidation (p<0.05) and a significant effect on changes in LDH levels due to increased lactate secretion (p<0.05). There was no significant correlation between changes in MDA and LDH levels (p=0.60) with a negative correlation, which means that the more significant the change in MDA levels, the lower the LDH level.